(untitled) (Journal of Economic Research & Business Administration, 2018)
The development of market relations in the agro-industrial complex of Kazakhstan, with its multistructure economy, should be ensured by the use of new methods of managing agricultural production. Agricultural production is a complex system that requires an appropriate scientific organization and fullfledged management. Specificity of agricultural production and management features of enterprises of the agro-industrial complex (AIC) in the context of the State program for the development of agriculture necessitate the improvement of accounting and control of costs to ensure financial stability and investment attractiveness of AIC’s enterprises. The main task of management accounting of the process of agricultural production is to scientifically substantiate the formation of individual costs of the agricultural organization for specific production facilities and determine its cost. In this regard, the purpose of the researching is to develop proposals to improve the accounting of cost formation and the calculation of the cost of dairy products. The methodology of the research is based on the studying of the methodology of management accounting and cost control in the process of calculating the cost of agricultural products. In this work, methodology has proposed for calculating the cost of production of dairy cattle at cost centers which are highlighted in business-processes in accordance with the physiological groups of animals. This technique allows you to reduce the cost of dairy products, as it will allow you to take into account all factors affecting the value of production costs The scientific significance of the research conducted in the article is to develop a set of theoretical and practical recommendations on the organization and methodology of management accounting, analysis and control of costs in the agricultural organization. In particular, the proposed methodology for calculating the cost of production of dairy farming in the cost centers, allows you to calculate the cost of production at the level of variable costs for business processes of dairy farming, which creates a relevant information base for managers. The proposed methodology for organization of management accounting and analysis will allow each agricultural organization to choose a strategy for the development of planning and coordination of management decisions for a long period, provide owners and managers of all levels of management with complete, prompt and reliable information on the activities of the agricultural organization.